Determination of Firm Value with Dividend Policy as Moderation Variable: Evidence Islamic Banking in the World - Indah Nur Hikmatus Shoumi; Guntur Kusuma Wardana (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2024)
Islamic banking is a company sector that dominates the global Islamic economic industry. To hold it, Islamic banking has to do a lot. One of which is to grow the value of the company. This research aims to identify factors that have an effect on company value in Islamic banking companies in the world. The company value factors studied are profitability (ROE), leverage (DER), company size, and dividend policy (DPR) as moderating variables. To determine the sample, researchers used purposive sampling by selecting 20 Islamic banks registered with the Islamic Financial Service Board (IFSB). Descriptive statistical analysis and moderated regression analysis are used as analysis methods. The results of this research show that profitability and company size have a significant effect on the value of Islamic banking companies. Leverage does not have a significant effect on the price of Islamic banking agencies. Dividend policy as a moderating variable does now not show significant results so it cannot moderate the connection between profitability, leverage and company size on the value of Islamic banking firms. Simultaneously, the variables profitability, leverage, firm size and dividend policy significantly impact the value of Islamic banking companies.